Pemanfaatan Shopee sebagai Toko Online untuk Meningkatkan Pangsa Pasar Produk UMKM di Desa Plelen - Aria Mulyapradana; Ary Dwi Anjarini; Aghus Jamaludin Kharis; Muhammad Nur Furqon Hidayat; M. Saadil Imtiyas (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The minimal use of technology in marketing products from small business actors in Plelen Village has an impact on the branding of the product which is less well known and the sales turnover is not optimal. The purpose of this activity is to increase the understanding and skills of small business actors about online marketing strategies, increase the reach of marketing areas, and increase sales turnover. The methods used were interviews, observations, lectures, discussions, practices and evaluation of activities and involved 34 MSME business actors in Plelen Village. The results of this activity show that MSME business actors are very enthusiastic about participating in the training because they have just received training to develop their business for the first time and have begun to switch to online media in marketing their products. This activity ran well and smoothly, it is hoped that after participating in this activity participants can increase sales turnover and market their products more widely.